Community Participation in the Climate Village Programme Based on Good Environmental Governance - Dea Salsabilla; Aldri Frinaldi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
This study aims to analyse the relationship between Human Resource Management (HRM) and the level of community engagement in the implementation of the Climate Village Programme based on Good Environmental Governance in the City of Padang. This approach emphasises capacity building, the organisation of roles, and the development of social competencies, which have implications for the quality of public contributions at every stage of the programme. This study employs a descriptive qualitative method, utilising data collection techniques such as in-depth interviews and documentary analysis. The data were subsequently analysed using the MDAP (Manual Data Analysis Procedure) technique. The findings indicate that community engagement remains at a fluctuating level and is not yet sustainable, influenced by economic incentives, the role of local leadership, and government policy interventions. On the other hand, the main barriers include limited economic resources, low ecological awareness, and suboptimal dissemination of programme information. These findings underscore the need for the systematic strengthening of MSDM practices to enhance the quality of public engagement through capacity building, cross-actor coordination, and more structured participation management to support the realisation of sustainable environmental governance.